2016
DOI: 10.1097/gco.0000000000000298
|View full text |Cite
|
Sign up to set email alerts
|

The urinary microbiota: a paradigm shift for bladder disorders?

Abstract: Purpose of Review A resident microbial community (the female urinary microbiota, FUM) exists within the female bladder of many adult women. Information about the FUM is likely to modify the diagnosis, prevention and treatment of adult women with urinary disorders. This review highlights key findings from recent literature relevant to adult, non-pregnant women. Recent Findings Similar to other human microbial communities, the FUM varies in its characteristics, including organism diversity and predominant orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 40 publications
(55 reference statements)
1
30
0
2
Order By: Relevance
“…Finally, with regard to updated UTI therapeutics, one must consider an impending paradigm shift regarding the “normal” state of the bladder – which has long been assumed to be sterile [95]. Enhanced culture techniques, as well as metagenomics on catheter-collected samples, have detected urinary bacteria in healthy and asymptomatic women [96].…”
Section: Next-generation Therapeuticsmentioning
confidence: 99%
“…Finally, with regard to updated UTI therapeutics, one must consider an impending paradigm shift regarding the “normal” state of the bladder – which has long been assumed to be sterile [95]. Enhanced culture techniques, as well as metagenomics on catheter-collected samples, have detected urinary bacteria in healthy and asymptomatic women [96].…”
Section: Next-generation Therapeuticsmentioning
confidence: 99%
“…Other studies have revealed associations between bladder bacteria and post-operative and post-instrumentation UTIs [ 96 , 97 ], urgency urinary incontinence [ 98 , 99 ], and response to overactive bladder treatment [ 100 ]. These findings suggest that the urinary tract possesses its own protective microbiota and that disruption (dysbiosis) of this community results in LUT symptoms (for recent reviews, see [ 101 103 ]).…”
Section: Cell Populations In or Associated With The Lutmentioning
confidence: 99%
“…Although the vast majority of genitourinary bacteria, which includes bacteria from the urethra, vagina, vulva, and bladder, cannot be cultured by standard clinical microbiology urine culture methods [ 7 , 8 ], they can be identified using high throughput 16S rRNA sequencing or new enhanced urine culture techniques [ 2 , 4 , 8 10 ]. The presence of urinary bacteria does not indicate UTI, as the bacteria that comprise the resident urinary microbiome differ from those associated with clinical UTIs [ 5 , 6 , 11 , 12 ]. While few studies have examined the diversity of the urine microbiome, current evidence links microbial diversity in catheterized urine specimens with urgency urinary incontinence (UUI) and response to treatment for lower urinary tract symptoms, especially those associated with UUI [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%